Fast quantification of nanorod geometry by DMA-spICP-MS. Issue 7 (27th February 2019) - Tan, Jiaojie; Yang, Yong; El Hadri, Hind; Li, Mingdong; Hackley, Vincent A.; Zachariah, Michael R.
Abstract : Fast, quantitative measurement of nanorod dimensions using tandem ion mobility spectrometry-single particle inductively coupled mass spectrometry. Abstract : A fast, quantitative method for determining the dimensions of nanorods ( i.e., length and diameter) is described, based on hyphenation of differential mobility analysis (DMA) with single particle inductively coupled plasma mass spectrometry (spICP-MS). Seven gold nanorod samples with different dimensions (diameters 11.8 nm to 38.2 nm, aspect ratios 1.8 to 6.9) were used to validate the method. We demonstrate that DMA-spICP-MS can (1) achieve quantification of both length and diameter comparable with TEM analysis, (2) make statistically meaningful measurements in minutes at low concentrations (<10 8 mL −1 ) and (3) separate nanorods from spheres and quantify the geometry of each population. A robustness analysis of this method was performed to evaluate potential biases in this approach.